Teaching practices that promote student learning: Five experiential approaches - Scott Donald Wurdinger; Jennifer Louise Bezon (University of Windsor, 2009)
University students are disengaged with learning. One reason is because educators continue to overuse the lecture format, which creates a situation where students engage in other tasks, such as sending text messages to their friends, instead to listening to the information being given by the instructor. If institutions and educators want to improve learning environments and increase retention rates, it is argued that they should consider embracing more active methods of learning that inspire and motivate students to learn. Five innovative teaching approaches discussed in this article include: project-based learning, problem based learning, service learning, place-based education, and active learning. Practical considerations are provided to help educators understand how to use and apply these approaches. It is contended that using these five innovative practices at the university level will help inspire and motivate students to learn, resulting in more exciting classrooms and a better-educated society.